ANALISIS SIKLUS TEORI PEMBERLAKUAN HUKUM ISLAM PADA PENGUATAN REGULASI HUKUM EKONOMI SYARIAH - Fadliah Mubakkirah; Dwi Utami Hudaya Nur; Ahmad Arief (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2022)
This study examines the theories of the application of Islamic law that were born from the thoughts of Islamic law experts, namely the theory of receptie exit, existence, and eclecticism. The presence of theories from Islamic law thinkers is an illustration of the cycle of legal thought in Indonesia, which started from the independence of Indonesia. Interestingly, there is no correlation between the application of Islamic law in all aspects, especially in the field of economic law. The discussion of the field of economic law only began to develop in the 1990s, followed by the issuance of regulations related to Islamic economics. Seeing this phenomenon, the research question in this paper was